Penerapan Program Sekolah Ramah Anak Untuk Mendukung Pengasuhan Positif Pada Anak Usia Dini - Suci Rahmadani; Malik, Lina Revilla (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
Early Childhood Education (PAUD) is an important stage in building a child's personality and character. This research aims to examine the implementation of the Child Friendly School (SRA) program at KB Al Mardhiyyah 3 Samarinda in supporting positive parenting. Using a descriptive qualitative approach, data was collected through interviews, observation and documentation involving school principals, teachers and parents. The research results show that the implementation of SRA in this school includes managing a safe physical environment, positive parenting by teachers, play-based learning, parenting programs, and promoting a culture of anti-violence. Supporting factors for success include the principal's commitment, teacher training and parental involvement, while the main challenges are the low awareness of some parents about positive parenting and limited facilities due to lack of financial support. This research concludes that SRA at KB Al Mardhiyyah 3 has succeeded in creating a child-friendly educational environment and supporting children's growth and development holistically, although they still face obstacles that require innovative strategies.